Hybrid Vigour and Combining Ability in Biofortified Maize (Zea mays L.) - Vedanchiya, K. K.; Soni, N. V.; Patel, R. M.; Patel, J. M.; Donga, A. R.; Dasalania, J. P.; Patel, J. B. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during winter season of 2020–2021 and rainy season of 2021 at Maize Research Station, Sardarkrushinagar Dantiwada Agricultural University, Bhiloda, Gujarat, India. The aim of the study was to assess magnitude of heterosis and combining ability of forty-five single cross hybrids developed by half-diallel mating design involving ten parents and two standard checks. The field experiment was laid out in randomized block design with three replications. The heterosis, combining ability and components of genetic variance were studied for diverse thirteen characters. The analysis of variance revealed that mean square values of genotypes were significant for all the characters which indicated the existence of considerable amount of genetic variation in genotypes for all the characters. Among single crosses, IMR-76×IMR-58 exhibited maximum mean and desired SCA effect and standard heterosis for β-carotene and IMR-53×IMR-72 for kernel yield. The general and specific combining ability variances observed highly significant for all traits except days to tasseling (only additive gene action), anthesis-silking interval and shelling percentage (only non-additive gene action). The σ2A/σ2D ratio indicated that preponderance of non-additive gene action for the inheritance of these characters suggesting due weightage should be given to heterosis breeding for genetic improvement of these traits. The crosses namely IMR-52×IMR-72 and IMR-51×IMR-58 presented significant heterosis for days to maturity, grain yield, iron and β-carotene content.